Sistem Pendukung Keputusan Pemilihan Pemasok Tahu Untuk Industri Tahu Bakso Menggunakan Metode Simpleadditive Weighting - Nugraha, Habib Rosyid Pandu; Mustafidah, Hindayati (Jurnal Teknologi Informasi (JUTECH), 2020)
One type of processed tofu that is popular with the public is tofu meatballs. The high demand for ordering tofu meatballs makes industrial owners have to produce it regularly every day. A large number of available tofu suppliers require the meatball tofu industry to be selective in choosing suppliers. The selection of the right raw materials will determine the quality of a production result, as well as assessing the quality of raw materials for tofu meatballs, namely tofu, which depends on the processing process. The process of selecting the quality of the tofu raw material can be assisted by a Decision Support System (DSS) computer program. This SPK helps business owners know meatballs to determine suppliers of tofu according to predetermined criteria. The criteria used are price, size, supply ability, taste quality, aroma quality, color quality, density quality. The SPK method used is Simple Additive Weighting (SAW). Based on testing with several alternative suppliers, it is obtained the ranking results and recommendations of suppliers selected according to the capacity of the tofu needs every day.